Pembuatan Website untuk Layanan Pemesanan Catering ELLA - Ariel Ronaldo Santoso; Agustinus Noertjahyana; Yulia Yulia (Jurnal Infra, 2016)
Speed is very needed by humans, because humans increasingly busy in work. Speed is important for humans who wants to support the desire of almost instantaneous. Some business opportunities that take advantage of technological advances which can be seen more and more business transactions are done online. The existence of e-commerce as GoFood, Food Panda, McDelivery, PHD, KFC Online is an alternative promising business to be applied in the era of technological development today, because e-commerce provides much convenience for both parties, either from the seller or from the buyer. Based on this background Catering ELLA seeks to create a website booking service and administration. The website is expected to create comfort and speed in the process of ordering food. The entire purchase feature to report all incorporated into a system that is not bothersome owner and reduce the risk of human error. Overall a website created in accordance with the needs of catering and users. Users feel the speed and in the process of purchasing food for catering and administrative processes.